Analisis Sistem Pencahayaan Pada Lantai 3 Gedung Kuliah Umum Institut Teknologi Sumatera - Khoirun Naimah; Abri Rahmatullah; M Azzam As Tsabit; Muqqafa Akbar P; Kamilah; Javeni Eysama Lumban G; Nuril Hidayat; M Allezandro Alghozi; Reuben Damara; Aldhi S; Ardian S (Sekolah Tinggi Teknik PLN, 2023)
Various regulations and standards have been issued by various authorities to support and increase the efficiency of energy use and manage energy conservation activities. Energy conservation is the obligation of all parties, including from the side of energy users in buildings, including one of them is the ITERA Public Lecture Building which is used mostly for classrooms, but there is no data on the quality of the lighting system. Therefore, this study aims to analyze the lighting system (energy consumption and lighting level) on the 3rd Floor of the ITERA General Lecture Building using the energy audit method. From the results of the study, it was found that the total energy consumption in the artificial lighting system (lamps) was 798.72 kWh/month, and the lighting level met the minimum limits of SNI 6197-2020, but out of 11 classrooms there were 7 rooms that were too much larger than SNI 6197-2020. So that the saving opportunity that can be done is to change the awareness of room energy users by reducing the length of time the lamp is used and prioritizing the use of natural light in the morning and afternoon so that it can save energy use by up to 34%.